Using the Net-Map tool to analyze stakeholder networks in the city region food systems of seven European cities - Leimkühler, Melissa; Specht, Kathrin; Schröter, Barbara; Wissmann, Anna; Iodice, Chiara; Fox-Kämper, Runrid; Steines, Ann-Kristin; Monticone, Francesca; Samoggia, Antonella; Modarelli, Giuseppe Carlo; Reynaud-Desmet, Lélia; Curtis, Adam; et al. (Frontiers in Sustainable Food Systems, 2024)
The current global food system is characterized by anonymity in the value chain, global food trade, loss of knowledge about food sources and a distant producer-consumer relationship. In addition, the negative environmental impacts of the agricultural sector, such as pollution, degradation of soil and water quality, loss of biodiversity and significant greenhouse gas emissions, make this sector a major driver of climate change. In contrast, the city region food system (CRFS) approach captures the complexity of a food system and its actors at the local level. It aims to meet the requirements of sustainable transformation along the food value chain and offers an alternative approach to the challenges of the global food system. However, the actors and their relationships in CRFS are rarely analyzed. To fill this gap this study focuses on analyzing CRFSs as networks using the Net-Map tool to study different CRFSs in seven European cities (Bologna, Naples, Lansingerland, Tenerife, Oslo, Dortmund, and Romainville). The aim of this paper is to concentrate on the method and to show how the Net-Map tool can effectively support the evaluation of the CRFS by identifying different actor roles, recognizing patterns of relationships. Additionally, the strengths and weaknesses of the network can be assessed by a strengths, weaknesses, opportunities and threats (SWOT) analysis. The paper highlights the limitations, advantages and practical use of the Net-Map tool and discusses potential transferability to other case studies.